On farm production of Trichoderma harzianum using organic matter - and Y.R. SARMA, KA SAJU, M. ANANDARAJ (Indian Phytopathology, 2002)
Addition of Trichoderma herzienum into organic media like neemcake, coirpith, farmyard manure and decomposed coffee pulp caused an immediate increase in the population upto 3 days. Population increase was observed at all the different proportions of initial inoculum levels tried. It also showed similar trends at different locations. Increase in the total population density of T. harzianum in the media suggests that competition by native fungi in non-sterile carrier media was not a limiting factor in colonization of the media by the antagonist. Soil amended with organic materials like neemcake, coircompost, farmyard manure and Gliricidia leaves showed better growth and survival of antagonist than in soil alone. The carrier materials like neemcake, coirpith, farmyard manure and decomposed coffee pulp serve as nutrient additives to the crop in addition to inoculum production they support.